Head Posture and Neck Pain of Chronic Nontraumatic Origin: A Comparison Between Patients and Pain-Free Persons - Silva, Anabela
Head Posture and neck pain of chronic nontraumatic origin: a comparison between patients and pain-free persons. Arch Phys Med Rehabil 2009;90:669-74. Objective: To compare standing head posture measurements between patients with nontraumatic neck pain (NP) and pain-free individuals. Design: Single-blind (assessor) cross-sectional study. Setting: Hospital and general community. Participants: Consecutive patients (n=40) with chronic nontraumatic NP and age- and sex-matched pain-free participants (n=40). Interventions: Not applicable. Main Outcome Measures: Three angular measurements: the angle between C7, the tragus of the car, and the horizontal; the angle between the tragus of the ear, the eye, and the horizontal; and the angle between the inferior margins of the right and the left ear and the horizontal were calculated through the digitization of video images. Results: NP patients were found to have a significantly smaller angle between C7, the tragus, and the horizontal, resulting in a more forward head posture than pain-free participants (NP, mean +/- SD, 45.4 degrees +/- 6.8 degrees; pain-free, mean +/- SD, 48.6 degrees +/- 7.1 degrees; P<.05; confidence interval [CI] for the difference between groups, 0.9 degrees-6.3 degrees). Dividing the Population according to age into younger (<= 50y) and older (>50y) revealed an interaction, with a statistically significant difference in head posture for younger participants with NP compared with younger pain-free participants (NP, mean +/- SD, 46.1 degrees +/- 6.7 degrees; pain-free, mean +/- SD, 51.8 degrees +/- 5.9 degrees; P<.01; CI for the difference between groups, 1.8 degrees-9.7 degrees) but no difference for the older group (NP, mean +/- SD, 44.8 degrees +/- 7.1 degrees; pain-free, mean +/- SD, 45.1 degrees +/- 6.7 degrees; P>.05; CI for the difference between groups, -4.9 degrees-4.2 degrees). No other differences were found between patients and pain-free participants. Conclusions: Younger patients with chronic nontraumatic NP were shown to have a more forward head Posture in standing than matched pain-free participants. However, the difference, although statistically significant, was perhaps too small to be clinically meaningful.